COENOFLORA OF ADONIS VERNALIS L. IN NORTHERN KAZAKHSTAN - Sultangazina G.J.; Kuprijanov А.N.; Kuprijanov О.А.; Beyshov R.S. (Scientific Journal of Pedagogy and Economics, 2020)
The current article presents the results of the study made on Adonis vernalis L. coenoflora of Northern Kazakhstan. The materials have been obtained in the course of field research considering the literary data. The list of Adonis vernalis L. flora discovered in Northern Kazakhstan is based on detailed route studies. The coenoflora of Adonis vernalis L. in Northern Kazakhstan includes 140 species belonging to 31 families and 96 genera. The leading families are Artemisia, Veronica, Achillea, Galatella, Lathyrus, Potentilla, Seseli, Silene. The majority of species belongs to perennial species, annuals and biennials are represented by six species, and there is only one ephemeral species. Woody and semi-woody plants are represented by three trees, five shrubs and one semishrub. Among the herbaceous plants there are more long-rooted and stem-rooted species. The coenoflora mainly consists of mesophytes (68 species) and xeromesophytes (57 species). There are 15 species of xerophytes, which makes 10,7%. A little number of xerophytes proves meadow and meadow-steppe nature of the coenoflora